Impact of acute infarct-related artery patency before percutaneous coronary intervention on 30-day outcomes in patients with ST-segment elevation myocardial infarction treated with primary percutaneous coronary intervention in the EUROMAX trial. Issue 6 (1st September 2018) - Rakowski, Tomasz; Dudek, Dariusz; van 't Hof, Arnoud; Ten Berg, Jurrien; Soulat, Louis; Zeymer, Uwe; Lapostolle, Frederic; Anthopoulos, Prodromos; Bernstein, Debra; Deliargyris, Efthymios N; Steg, Philippe Gabriel
Abstract: Aims: Early infarct-related artery patency has been associated with improved outcomes in patients with ST-segment elevation myocardial infarction treated with primary percutaneous coronary intervention. However, it is unknown whether this relationship persists in contemporary practice with pre-hospital initiation of treatment, use of novel P2Y12 inhibitors and frequent use of drug-eluting stents. The purpose of the study was to determine the impact of early infarct-related artery patency on outcomes in the contemporary EUROMAX trial. Methods and results: A total of 2218 patients were enrolled. The current analysis was done on 1863 patients who underwent percutaneous coronary intervention and had infarct-related artery patency data. Thirty-day outcomes were compared according to infarct-related artery flow before percutaneous coronary intervention (Thrombolysis in Myocardial Infarction (TIMI) flow 0/1 vs . TIMI flow 2/3), and interaction with antithrombotic strategy was examined. A patent infarct-related artery (TIMI flow 2/3) was present in 707 patients (37.9%) and was associated with a higher rate of final TIMI 3 flow grade (98.9 vs . 92.6%; p <0.001). At 30 days, a patent infarct-related artery was associated with lower rates of cardiac death (1.3% vs . 2.9%; p =0.026) and the composite of death or myocardial infarction (2.7% vs . 4.6%; p =0.039). There were no interactions between antithrombotic treatment and the impact of infarct-related artery patency on cardiac death, myocardial infarction, or the composite of death or myocardial infarction (Breslow–Day interaction p -values of 0.21, 0.33 and 0.46, respectively). Conclusion: Despite evolution in primary percutaneous coronary intervention strategies, early infarct-related artery patency is still associated with higher procedural success and improved clinical outcomes. The choice of antithrombotic strategy did not interact with the benefits of a patent infarct-related artery at presentation.